2012
DOI: 10.12973/eurasia.2012.824a
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of Science Teaching Philosophies and Practice in Early Career Primary Teaching Graduates

Abstract: Terms and conditions for use: By downloading this article from the EURASIA Journal website you agree that it can be used for the following purposes only: educational, instructional, scholarly research, personal use. You also agree that it cannot be redistributed (including emailing to a list-serve or such large groups), reproduced in any form, or published on a website for free or for a fee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This points to a degree of pedagogic knowledge and raises the question of how these skills could be used to improve their science teaching? While research indicates that there are very few science components in initial teacher education programmes (Bartholomew, Anderson & Moeed 2012) which explains their poor science knowledge, the topics the teachers selected to teach were fairly simple and taught year after year. It would appear that an experienced teacher could prepare herself better with regard to scientific knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This points to a degree of pedagogic knowledge and raises the question of how these skills could be used to improve their science teaching? While research indicates that there are very few science components in initial teacher education programmes (Bartholomew, Anderson & Moeed 2012) which explains their poor science knowledge, the topics the teachers selected to teach were fairly simple and taught year after year. It would appear that an experienced teacher could prepare herself better with regard to scientific knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The teaching statement is sometimes referred to as "statement of teaching philosophy" and captures the statement's purpose of teachers in the classroom (Oxley, 2015). Overall, from 28 reviewed articles, authors find some articles using the term in philosophy of science teaching (2 studies) (Matthews, 1988;Pospiech, 2003), philosophy of physics (6 studies) (Seeger, 1960;Crowe, 1999;Noll, 2002;Scott, 2015;Rajapaksha & Hirsch, 2017;Bächtold & Munier, 2019), philosophy of science in teaching (5 studies) (Terhart, 1988;Matthews, 1990;Elkana, 2000;Teixeira et al, 2012;Henke & Höttecke, 2015), teaching philosophy (2 studies) (Kurki-Suonio, 2011;Bartholomew et al, 2012), teaching statement (1 study) (Oxley, 2015), and teaching philosophy statement (12 studies) ( Beatty et al, 2009a( Beatty et al, , 2020a( Beatty et al, , 2020bGrundman, 2006;Eierman, 2008;Kearns & Sullivan, 2011;Alexander et al, 2012;Drolet, 2013;Supasiraprapa & De Costa, 2017;Laundon et al, 2020;Merkel, 2020;Trellinger Buswell & Berdanier, 2020). The most common words mentioned by the researchers on this issue are the teaching philosophy statement (TPS).…”
Section: Resultsmentioning
confidence: 99%
“…In line with this, this review has also discovered that not much concentration has been given to practitioners such as teachers and lecturers across the years of research studies in STEM education. Bartholomew, Anderson and Moeed (2012) revealed that content knowledge alone does not make a teacher. According to Kabilan (2003), Malaysian teachers need to learn continuously because continuous learning by teachers holds the key to the transformation of Malaysian schools, training, and preparing its learners to face challenges apart from improving the learners' performances.…”
Section: Discussionmentioning
confidence: 99%